To speak with the other's voice: reducing asymmetry and social distance in mental health care admission interviews - Bonnin, Juan Eduardo (2014)
The aim of this article is to examine the case of adoption of characteristic features of the interlocutor's ‘voice’ in mental health care admission interviews at a public hospital in Buenos Aires, Argentina. We observed ethnographically that ‘speaking with the Other's voice’ is a strategy adopted by psychoanalysts to achieve clinical goals, though they overlook its wider implications and contradictions as it involves both professionals and patients. We will argue that patients adopt bureaucratic and psychiatric terms in order to decrease asymmetry and reorient the activity conducted between the professional and the client. On the other hand, professionals tend to consider social class, age, ethnicity or religion when adopting the patient's voice in an attempt to decrease social distance. These strategies are employed to accomplish different goals during the interview: to the patient, it is a way to show competence in the activity of medical consultation, indexing the highly valued voices of state institutions and psychiatric knowledge; to the professional, it is a strategy to achieve clinical goals by decreasing social distance and enhancing transference. Analysis will show the unequal distribution of voicing options for participants: while patients attempt to reduce asymmetry despite social distance, psychotherapists try to decrease social distance but maintain asymmetry. In conclusion, wider implications will be discussed for intergroup communication between professionals and clients.